Effect of Ultraviolet Water Treatment on Survival and Growth of Escherichia coli in Recirculating Hydroponic Systems - Markanna Moore; Teng Yang; Majid Jaberi Douraki; Cary Rivard; Eleni Pliakoni; Londa Nwadike; Manreet Bhullar (Journal of Food Protection, 2025)
Hydroponic nutrient solution can serve as a distribution mechanism for human pathogens to spread throughout an indoor farm since many hydroponic farms do not include water treatment during the crop growth period. Contamination can be introduced to recirculating nutrient solution through various routes, including growing media and worker contact. In leafy green production, it is common for nutrient solution to inadvertently contact produce during harvest or packaging. Therefore, it is critical that such water be free of human pathogens. Ultraviolet (UV) treatment of water could reduce contamination in nutrient solution without disrupting production or introducing new chemical inputs to the nutrient solution.This study investigated the survival of generic Escherichia coli (E. coli) in hydroponic systems and assessed the efficacy of a 254 nm UV-C light treatment for E. coli reduction. Romaine lettuce was grown in hydroponic systems for six weeks. E. coli was inoculated into hydroponic nutrient solution at 6.02 average log CFU/mL UV-C treatments of water were performed biweekly. Hydroponic controls grew plants but received no UV-C treatment, and nonhydroponic controls neither grew plants nor received treatment. The efficacy of the treatment was assessed in terms of bacterial reduction in log CFU/mL.The UV-C treatments resulted in significant (P < 0.001) reductions of 1.4–1.5 log10 CFU/mL of E. coli in the nutrient solution. However, the E. coli population declined naturally over the weeks following the inoculation, independent of the UV-C treatment. Survival of E. coli beyond one week is limited in the nutrient solution. Still, UV-C treatment has the potential to be used as a preventative safeguard for the microbial safety of the hydroponic production system by reducing contamination within the nutrient solution during crop growth. This can help maintain the safety of hydroponically grown fresh produce and reduce the likelihood of future outbreaks.